Mesocrystalline Ta2O5 nanosheets supported PdPt nanoparticles for efficient photocatalytic hydrogen production. (26th April 2018) - Yu, Xin; Liu, Guangbo; Li, Wei; An, Li; Li, Zhonghua; Liu, Jiawen; Hu, Pingan
Abstract: We successfully synthesized mesocrystalline Ta2 O5 nanosheets supported bimetallic PdPt nanoparticles by the photo-reduction method. The as-prepared mesocrystalline Ta2 O5 nanosheets in this work showed amazing visible-light absorption, mainly because of the formation of oxygen vacancy defects. And the as-prepared bimetallic PdPt/mesocrystalline Ta2 O5 nanaosheets also showed highly enhanced UV–Vis light absorption and highly improved photocatalytic activity for hydrogen production in comparison to that of commercial Ta2 O5, mesocrystalline Ta2 O5 nanosheets, Pd/mesocrystalline Ta2 O5 nanosheets and Pt/mesocrystalline Ta2 O5 nanosheets. The highest photocatalytic hydrogen production rate of PdPt/mesocrystalline Ta2 O5 nanaosheets was 21529.52 g −1  h −1, which was about 21.2 times of commercial Ta2 O5, and the apparent quantum efficiency of PdPt/mesocrystalline Ta2 O5 nanaosheets for hydrogen production was about 16.5% at 254 nm. The highly enhanced photocatalytic activity was mainly because of the significant roles of PdPt nanoparticles for accelerating the charge separation and transport upon illumination. The as-prepared PdPt/mesocrystalline Ta2 O5 nanaosheets in this work could serve as an efficient photocatalyst for green energy production. Highlights: PdPt/mesocrystalline Ta2 O5 nanosheets were synthesized. The composites showed highly enhanced UV–Vis light absorption. The composites showed superior photocatalytic activity.